2012
DOI: 10.3390/s120100905
|View full text |Cite
|
Sign up to set email alerts
|

Sheathless Size-Based Acoustic Particle Separation

Abstract: Particle separation is of great interest in many biological and biomedical applications. Flow-based methods have been used to sort particles and cells. However, the main challenge with flow based particle separation systems is the need for a sheath flow for successful operation. Existence of the sheath liquid dilutes the analyte, necessitates precise flow control between sample and sheath flow, requires a complicated design to create sheath flow and separation efficiency depends on the sheath liquid compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
71
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 50 publications
1
71
0
1
Order By: Relevance
“…Among the single‐layered PDMS‐based devices, similar kind of focusing is not reported before. Due to the utilization of the principal component of ARF, the present device successfully operated for particle separation at net flow rate up to 1.3 mL min −1 , which is ≈100 times higher than used in previously reported SAW devices 20, 23, 31, 32, 37, 38, 42, 43, 47, 48. The throughput of the proposed device can be further improved with ease by increasing the width of the microchannel since the microchannel is placed directly on the IDT.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Among the single‐layered PDMS‐based devices, similar kind of focusing is not reported before. Due to the utilization of the principal component of ARF, the present device successfully operated for particle separation at net flow rate up to 1.3 mL min −1 , which is ≈100 times higher than used in previously reported SAW devices 20, 23, 31, 32, 37, 38, 42, 43, 47, 48. The throughput of the proposed device can be further improved with ease by increasing the width of the microchannel since the microchannel is placed directly on the IDT.…”
Section: Introductionmentioning
confidence: 85%
“…The proposed design provided an additional advantage of utilizing both the horizontal and stronger vertical components of the ARF acting on the particles. The height and width of the microchannel did not significantly alter the device performance, unlike the SSAW‐based devices, in which the microchannel aspect ratio significantly affected the locations of the pressure nodes and antinodes 22, 39, 40, 42. The present device utilized a comparatively low input power because the energy loss to PDMS walls was minimal as the IDT was directly exposed to the fluid and both the vertical and horizontal components of the ARF were employed.…”
Section: Introductionmentioning
confidence: 98%
“…The device is built from two identical interdigital transducers (IDTs) with a polydimethylsiloxane (PDMS) microchannel located symmetrically between them. 8,11,44,60,61 The mechanism of particle manipulation based on phase-shifting of an acoustic standing wave is illustrated in Fig. 1b-d.…”
Section: Methodsmentioning
confidence: 99%
“…43 Increasing the frequency of the field, transducer dimensions and therefore the device size can be reduced and successful sorting can be achieved in microfluidic devices. 11,39,44 The Huang group showed that the efficiency of sorting can be increased by inclining the transducer at a specific angle to the flow direction 9 and the method was applied for the isolation of circulating tumor cells. 45 In recent years, dynamic acoustic approaches, where the time-averaged radiation force changes with time, have gained increasing interest for particle manipulation, and specifically for sorting.…”
Section: Introductionmentioning
confidence: 99%
“…The pressure is maximum at the antinode and minimum at the node. Due to this pressure differential, solid particles tend to reassemble and concentrate in zones of minimum acoustic potential energy, which is typically at the nodes [14]. In a microchannel multiple nodes could exist depending on the wavelength/frequency of the wave.…”
Section: Introductionmentioning
confidence: 99%